The Six Sigma Handbook, 5E - Pyzdek, Thomas; Keller, Paul A. (McGraw-Hill Education, 2019)
The most important reference to Lean Six Sigma?fully updated for the latest advances. This thoroughly revised, industry standard guide delivers all the information you need to apply Lean Six Sigma techniques and dramatically improve processes, profitability, sustainability, and long-term growth. Written by two of the foremost authorities in the field, the book contains full explanations of the latest lean, problem solving and change management principles and methods. You will discover how to build the best teams and foster effective leadership while maximizing customer satisfaction and boosting profits. The book includes coverage of the recently released Minitab 18. The Six Sigma Handbook, Fifth Edition covers: Building the responsive Six Sigma organization, Recognizing and capitalizing on opportunity, Data-driven management, Maximizing resources, Project management using DMAIC and DMADV, The define phase, The measure phase, Process behavior charts, Measurement systems evaluation, The analyze phase, The improve/design phase, The control/verify phase.